Synthesis and characterization of PEG assisted Znq2 compound for organic light emitting diode applications. (2020) - Bharathi Devi, V.; Andal, C.; Arulmozhichelvan, P.; Murugakoothan, P.
Abstract: Zinc (ii)-bis (8-hydroxyquinoline) (Znq2) and PEG assisted Znq2 compounds were synthesized by simple precipitation method. The crystal nature of title samples and 8-hydroxyquinoline was confirmed by Powder X-ray diffraction (PXRD). The FTIR analyze is used to find and assign the functional groups of Znq2 compounds. The optical property of 8- hydroxyquinoline, Znq2 and Znq2:PEG was confirmed by UV–vis-NIR spectroscopy with the determination of band gap value. The synthesized Znq2 and surfactant assisted PEG particles and 8-hydroxyquinoline were studied by photoluminescence spectra for OLED applications as emission and electron transport layers.